The Management Factor in Acquisition Performance - Norburn, David; Hall, Peter D. (Cranfield School of Management, 1986)
This paper reviews the "state of the art" of both theoretical development and empirical investigation concerning Mergers and Acquisitions. It classifies existing knowledge within three main areas: . pre-acquisition procedures - typologies of selection and decision making processes; . valuation activity - the, letermination of price and methods of payment; . success criteria - what should be measured. The review highlights the paucity of research as to the different effects of managerial behaviour and motivation upon acquisition outcomes, and therefore suggests a number of testable hypotheses in urgent need of investigation.
Submitted to Business and Policy Planning Division: 1986 National Academy of Management Conference, Chicago.